2010
DOI: 10.1186/1742-2094-7-67
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 modulates cytokine production in cultured mouse astrocytes

Abstract: BackgroundThe chemokine CCL2 (also known as monocyte chemoattractant protein-1, or MCP-1) is upregulated in patients and rodent models of traumatic brain injury (TBI), contributing to post-traumatic neuroinflammation and degeneration by directing the infiltration of blood-derived macrophages into the injured brain. Our laboratory has previously reported that Ccl2-/- mice show reduced macrophage accumulation and tissue damage, corresponding to improved motor recovery, following experimental TBI. Surprisingly, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 62 publications
5
31
0
Order By: Relevance
“…The only drastic decline observed between treatments concerned CCL2 (also known as MCP-1), whose secretion was decreased following IL-1 treatment in both midbrain and spinal cord cultures ( Figure 6A). This finding is in line with recent work showing a down regulation of this protein in cultures composed of primary inflammatory human astrocytes (Choi et al, 2014), and whose absence exacerbates the release of several pro-inflammatory cytokines including IL-6, G-CSF, IL-1 and CXCL1, indicating a negative regulatory role of CCL2 in neuroinflammation (Semple et al, 2010). In general, no dramatic differences in cytokine and chemokine secretions were observed between midbrain and spinal cord cultures treated with IL-1.…”
Section: Human Esc Midbrain and Spinal Cord Progenitor-derived Gfa Absupporting
confidence: 90%
“…The only drastic decline observed between treatments concerned CCL2 (also known as MCP-1), whose secretion was decreased following IL-1 treatment in both midbrain and spinal cord cultures ( Figure 6A). This finding is in line with recent work showing a down regulation of this protein in cultures composed of primary inflammatory human astrocytes (Choi et al, 2014), and whose absence exacerbates the release of several pro-inflammatory cytokines including IL-6, G-CSF, IL-1 and CXCL1, indicating a negative regulatory role of CCL2 in neuroinflammation (Semple et al, 2010). In general, no dramatic differences in cytokine and chemokine secretions were observed between midbrain and spinal cord cultures treated with IL-1.…”
Section: Human Esc Midbrain and Spinal Cord Progenitor-derived Gfa Absupporting
confidence: 90%
“…Previous studies using murine AD models have demonstrated that chemokine receptor systems such as CCR5 (36), CCR2 (37)(38)(39), and CX3CR1 (40)(41)(42)(43) can modulate the disease course by influencing microglial function, accumulation, and clustering (37,(40)(41)(42). In addition, a positive correlation between CXCL10 concentrations in the cerebrospinal fluid and cognitive impairment in AD patients has been demonstrated (44,45).…”
Section: Introductionmentioning
confidence: 97%
“…31 Although the mechanism has yet to be defined, inhibition of CCL2 also has been observed to promote pro-inflammatory cytokine production from astrocytes. 29,32 Taken together, these data suggest that to maximize blockade of macrophage infiltration and inflammation, it may be advantageous to target the receptor, CCR2, for which drugs have recently been generated. 33 We therefore investigated TBI outcomes in CCR2-deficient (Ccr2 -/ -) mice, using a controlled cortical impact model of experimental TBI.…”
mentioning
confidence: 98%